1994
DOI: 10.1055/s-2007-1001720
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Beta (IL-1β) Binds to Intact Porcine Thyroid Follicles, Decreases Iodide Uptake but has no Effect on cAMP Formation or Proliferation

Abstract: Interleukin-1 beta (IL-1 beta) is known to be involved in autoimmune thyroiditis. Since the results of different in vitro-studies on the effect of IL-1 on thyrocytes are controversial, our aim was to investigate the existence of specific binding sites for IL-1 beta and its influence on specific functions and growth of isolated porcine thyroid follicles ex vivo with a preserved iodide metabolism. For binding studies isolated thyroid follicles were incubated with 125I-IL-1 beta (213.5 nCi/ml) and with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Upon injection, IL-1␣ and IL-1␤ stimulate thyroid growth in rats (32), and IL-1␣ promotes the growth of a thyroid carcinoma cell line via Ca 2ϩ /calmodulin pathways (33). In contrast, the group of Gärtner found no effect of IL-1␤ on thyrocyte proliferation using a porcine thyroid follicle culture system (34). IL-6 was described as not affecting basal cell proliferation of FRTL-5 cells, it stimulated DNA-synthesis in a dose-dependent manner in the presence of TSH (35).…”
Section: Discussionmentioning
confidence: 99%
“…Upon injection, IL-1␣ and IL-1␤ stimulate thyroid growth in rats (32), and IL-1␣ promotes the growth of a thyroid carcinoma cell line via Ca 2ϩ /calmodulin pathways (33). In contrast, the group of Gärtner found no effect of IL-1␤ on thyrocyte proliferation using a porcine thyroid follicle culture system (34). IL-6 was described as not affecting basal cell proliferation of FRTL-5 cells, it stimulated DNA-synthesis in a dose-dependent manner in the presence of TSH (35).…”
Section: Discussionmentioning
confidence: 99%
“…The role of cAMP in IL-1 signal transduction is variable. Al though in some biological systems IL-1 in creases the level of cytosolic cAMP [18], in some cells IL-1 does not change cAMP levels [19][20][21] or may decrease them [22], In some cases, cAMP modulates or mimics effects of IL-1 [23,24], without mediating them. How ever, other effects of IL-1 seem to be indepen dent of cAMP [25,26], cAMP and IL-1 may even have opposing effects; thus, in human lung fibroblasts cAMP inhibits IL-l-induced IL-6 production [27], In the present study IL-1 had no detectable effect on the concentra tion SP-B mRNA, whereas cAMP significant ly increased SP-B mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid peroxidase (TPO) mRNA expression and protein content, important for the oxidation of iodide to iodine, is also directly affected by IL1 in human thyrocytes and rat thyroid FTRL-5 cells (Asakawa et al 1996, Gerard et al 2006. Moreover, IL1b impairs basal and TSH-stimulated uptake of iodide by the natrium/iodide symporter (NIS) in porcine thyroid follicles (Nolte et al 1994). The role of IL6 is less well established: one study showed that IL6 inhibits the TSHand cAMP-induced increase in TPO mRNA expression and T 3 secretion in thyrocytes obtained from Graves' disease patients (Tominaga et al 1991), while IL6 has only a minor effect on cultured human thyroid cells (Rasmussen et al 1991).…”
Section: The Effect Of Cytokines On Th Synthesismentioning
confidence: 99%